Analysis of Risk Factors for Tuberculosis Incidence in the Awaru Awangpone Public Health Center Working Area, Bone: An Analytical Observational Study - Ronny; Zulfikar Ali Hasan; Jasman; RH Kristina; Albina Bare (Gema Lingkungan Kesehatan, 2025)
Tuberculosis (TB) remains a global health challenge, particularly in regions with inadequate environmental conditions. This study aims to analyze the association between lighting, humidity, ventilation area, and residential density with TB incidence in the working area of Awaru Awangpone Public Health Center, Bone Regency. This analytical observational study used a cross-sectional design. Data were collected through direct observation and interviews, and statistical analysis was conducted using the Chi-Square test with a 95% confidence level (α = 0.05). The relationship between risk factors and TB incidence was measured using the Odds Ratio (OR) and 95% Confidence Interval (CI). The result show inadequate lighting was significantly associated with TB incidence (p = 0.032, OR = 1.10, 95% CI: 0.55–2.22). Ventilation area also showed a significant relationship with TB incidence (p = 0.031, OR = 5.25, 95% CI: 1.17–26.02). However, no significant association was found between humidity and TB incidence (p = 0.946, OR = 0.97, 95% CI: 0.45–2.11). Residential density was significantly related to TB incidence (p = 0.038, OR = 0.44, 95% CI: 0.76–3.08). Environmental factors, particularly lighting, ventilation, and residential density, play a crucial role in TB transmission.  These findings highlight the need for targeted interventions to improve living environments in high risk areas.